Custom-made ceria nanoparticles show a neuroprotective effect by modulating phenotypic polarization of the microglia - Zeng,F; Wu,Y; Li,X; Ge,X; Guo,Q; Lou,X; Cao,Z; Hu,B; Long,NJ; Mao,Y; Li,C (Angewandte Chemie International Edition, 2018)
The neuroprotective effect of ceria nanoparticles in the context of brain disorders has been explained by their antioxidant effect. However, the in-depth mechanism remains unknown. As resident immune cells in the brain, microglia exert a variety of functional reprogramming termed as polarization in response to stress stimuli. Herein, custom-made ceria nanoparticles were developed and found to scavenge multiple reactive oxygen species with extremely high efficiency. These nanoparticles drove microglial polarization from a pro-inflammatory phenotype to an anti-inflammatory phenotype under pathological conditions. Pretreatment of these nanoparticles changed the microglial function from detrimental to protective for the neuronal cells by blocking the pro-inflammatory signaling. This work not only helps to elucidate the mechanism of ceria-nanoparticle-mediated neuroprotection but also provides a new strategy to rebalance the immuno-environment by switching the equilibrium of the phenotypic activation of microglia.